Community Perceptions of Countries in The World Towards Corruption and Its Handling in Indonesia in The Last Five Years (2017-2022) - Yuli Noor Kusumawati; Mustofa Mustofa; Setyabudi Indartono (CV. Syntax Corporation Indonesia, 2024)
The Corruption phenomena in the World is important to analyze because corruption has decreased on quality of public services and economic productivity. This research aims to determine and analyze the level of corruption in the form of bribery and gratification in Indonesia from a world perspective involving 169 countries (76,350 respondents) during five years from 2017 until 2022. Analysis in this study using statistical tabulation methods has shown that the results of Corruption Perceptions explain that 87.8% of corruption (both high and medium level corruption) and 12.62% low level and no corruption) with domination actors of corruption are businessmen 94,76%, second of sequel is central governments at 94,51% respondents and the third of sequel is local government at 93,74% The risk of corruption in the form of law action that has a deterrent effect on corruption in Indonesia is still very weak, this is stated by 24.07% of respondents. Therefore, to reduce corruption, it is necessary to eliminate the culture of tribute to government officials, then in terms of the government must increase the integrity of public services, accompanied by firmness and independence of law enforcement officials.